Pendidikan Karakter Melalui Model Pembentukan Bank Sampah Berbasis Pesantren di PP Ibnu Sina Genteng Banyuwangi - Nurul Inayah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Abstract: Handling and correct waste management are very important to do at boarding schools. Boarding schools are now supposed to be a place to learn about the correct waste management, start to build awareness of the handling and waste management by establishing the bank trash-based boarding school. The purpose of this modeling is to: (1) to instill the awareness of students in SMK Avicenna who was in PP Avicenna on the cleanliness of the environment. (2) Provide learning on students about waste management, and continued to form the bank's trash, which hopefully will create a healthy and clean environment. (3) with the bank later this waste will be realized also the creativity of students learning with the utilization of waste.Keywords: Character education, creativity, Boarding, trash, waste management